Natives, Port of Spain, Trinidad B.W.I. - (:unkn) unknown (My University, 2008)
In this ancient photograph circa the early 1900s men, women and children of African descent and East Indians are gathered under a large tree. The East Indian women are dressed in cotton saris and the men are dressed in dhotis and kurtas.
Colour: Brown and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Postcards; East Indians--Trinidad and Tobago; Creoles--Trinidad and Tobago; Women--Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Children--Trinidad and Tobago; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Ethnic costume--India; Trees--Trinidad and Tobago